The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1051/0004-6361/201323226
|View full text |Cite
|
Sign up to set email alerts
|

Proper motions of the optically visible open clusters based on the UCAC4 catalog

Abstract: We present a catalog of mean proper motions and membership probabilities of individual stars for optically visible open clusters, which have been determined using data from the UCAC4 catalog in a homogeneous way. The mean proper motion of the cluster and the membership probabilities of the stars in the region of each cluster were determined by applying the statistical method in a modified fashion. In this study, we applied a global optimization procedure to fit the observed distribution of proper motions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
207
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(230 citation statements)
references
References 37 publications
16
207
5
Order By: Relevance
“…Kurtenkov et al (2016) used both kinematic and photometric criteria to select the most reliable members and recalculated proper motions for a sample of 15 open clusters. For some of the clusters their results differ significantly from the ones given by Dias et al (2014), and they suggested that the difference could be linked to a field star contamination effect. In the case of NGC 1647, Kurtenkov et al (2016) calculated a proper motion (µα cos δ, µ δ ) = (−1.13, −1.27) mas yr −1 whereas Dias et al (2014) obtained (µα cos δ, µ δ ) = (−0.74, −0.57) mas yr −1 .…”
Section: Ngc 1647mentioning
confidence: 63%
See 4 more Smart Citations
“…Kurtenkov et al (2016) used both kinematic and photometric criteria to select the most reliable members and recalculated proper motions for a sample of 15 open clusters. For some of the clusters their results differ significantly from the ones given by Dias et al (2014), and they suggested that the difference could be linked to a field star contamination effect. In the case of NGC 1647, Kurtenkov et al (2016) calculated a proper motion (µα cos δ, µ δ ) = (−1.13, −1.27) mas yr −1 whereas Dias et al (2014) obtained (µα cos δ, µ δ ) = (−0.74, −0.57) mas yr −1 .…”
Section: Ngc 1647mentioning
confidence: 63%
“…For some of the clusters their results differ significantly from the ones given by Dias et al (2014), and they suggested that the difference could be linked to a field star contamination effect. In the case of NGC 1647, Kurtenkov et al (2016) calculated a proper motion (µα cos δ, µ δ ) = (−1.13, −1.27) mas yr −1 whereas Dias et al (2014) obtained (µα cos δ, µ δ ) = (−0.74, −0.57) mas yr −1 . Our cluster proper motion centroid (µα cos δ, µ δ ) = (−0.85, −1.11) mas yr −1 is in between both values but slightly closer to the Kurtenkov et al (2016) result (|∆µ| = 0.32 mas yr −1 ).…”
Section: Ngc 1647mentioning
confidence: 63%
See 3 more Smart Citations